Criminological and forensic psychology - Gavin, Helen (Thousand Oaks, CA : SAGE Publications, 2018)
The second edition of Criminological and Forensic Psychology is an even more theoretically rigorous, practically relevant, engaging and fun introduction to this broad and fascinating field. It covers both the conceptual basis within which psychology knowledge is applied in forensic contexts and the practical applications of psychology to the criminal civil justice systems.
Keywords: Criminological; forensic psychology